Problematizing Facebook as a public sphere a case study of the Ondoy crisis as seen on Facebook - Dimaculangan, Camille Lector 1990- (2012)
"This paper seeks to problematize the realm of Facebook as a Public Sphere through a critical analysis of its ability to facilitate critical discourse as well as the underlying politics behind the Filipino membership base during the height of the Ondor crisis. The study is guided by the ideas forwarded by German sociologist Jurgen Habernas regarding the Public Sphere and its implications regarding social economic classes. The study will also refer to Michel Foucault and his ideas of power. The study will employ a textual analysis of content shared by Facebook users from various sectors of society during the height of the Ondoy crisis. Through the analysis of such content, it is the aim of this study to answer the question of whether or not Facebook functioned as a public sphere based on the ideas forwarded by Habermas. In the effort to bring the study in the Philippine context, this thesis will also provide an overview of Internet access and usage in the Philippines to discuss the status of Facebook in the Philippine online environment. By establishing these ground, this thesis attempts to problematize the idea of Facebook as a Public Sphere as observed via the Ondoy crisis."